2010
DOI: 10.1375/twin.13.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase-Like 5 (CDKL5) Mutation Screening in Rett Syndrome and Related Disorders

Abstract: Rett syndrome (RTT) is a severe neurodevelopmental disorder affecting females almost exclusively and is characterized by a wide spectrum of clinical manifestations. Mutations in the X-linked methyl-CpG-binding protein 2 (MECP2) gene have been found in up to 95% of classical RTT cases and a lesser proportion of atypical cases. Recently, mutations in another X-linked gene, CDKL5 (cyclin-dependent kinase-like 5) have been found to cause atypical RTT, in particular the early onset seizure (Hanefeld variant) and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…Previous studies of the CDKL5 disorder have also reported dysmorphic features including: large deep-set eyes, strabismus, high forehead, full lips, wide mouth, widely spaced teeth and a high palate. 1,4,5,7,13,18,20,22,25,26,[28][29][30]35 Dysmorphic features have been described in other conditions presenting with early-onset encephalopathy, such as those with FOXG1 mutations and in Pitt-Hopkins syndrome (PHS). In those with FOXG1 mutations, subtle, non-specific dysmorphic features have been reported, along with severe microcephaly, which is typical of FOXG1 syndrome but not common in individuals with the CDKL5 disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of the CDKL5 disorder have also reported dysmorphic features including: large deep-set eyes, strabismus, high forehead, full lips, wide mouth, widely spaced teeth and a high palate. 1,4,5,7,13,18,20,22,25,26,[28][29][30]35 Dysmorphic features have been described in other conditions presenting with early-onset encephalopathy, such as those with FOXG1 mutations and in Pitt-Hopkins syndrome (PHS). In those with FOXG1 mutations, subtle, non-specific dysmorphic features have been reported, along with severe microcephaly, which is typical of FOXG1 syndrome but not common in individuals with the CDKL5 disorder.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,5,7,13,18,20,22,25,26,[28][29][30]35 The presence of typical facial or other features could provide additional assistance in the clinical identification of individuals with a CDKL5 mutation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, truncations of the C-terminus seem to enhance its phosphorylation and cause its nuclear accumulation and activity [Rusconi et al, 2008]. Interestingly, recent data suggest that missense mutations negatively affecting the catalytic activity of CDKL5 could be associated with a more severe clinical picture than that caused by truncating mutations located in the last exons of CDKL5 that are predicted to truncate only amino acids of the CDKL5 COOH-terminus [Evans et al, 2005;Bahi-Buisson et al, 2008b;Russo et al, 2009;White et al, 2010].…”
Section: Functions Of the Cdkl5 Proteinmentioning
confidence: 99%
“…Mutations in the CDKL5 gene have been associated with the early-onset seizure variant of Rett syndrome, although the predominant phenotype is an epileptic encephalopathy. [3][4][5] The congenital variant is characterised by infantile hypotonia and developmental delay evident earlier than in classic Rett syndrome but causative mutations have previously rarely been identified in these patients. 6 Recent reports of microdeletions in the 14q12 region found in Rett syndrome patients have found a third gene, forkhead box protein G1 (FOXG1), to be highly associated with the congenital variant.…”
Section: Introductionmentioning
confidence: 99%